Channa striatus aqueous extract improved cognitive function in rats - Ab Aziz, Muhamad Faris (2012)
Channa striatus (Haruan) is a snakehead fish that is consumed traditionally in many Southeast Asian regions as a wound healing agent to relieve pain. The experiment was carried out to assess the effects of C. striatus aqueous extract on cognitive function in rats. The experiment involved a ten-week study to investigate the effects of C. striatus aqueous extract on spatial learning and memory in rats. Forty male Sprague-Dawley rats were randomly allocated into four treatment groups of 10 animals each. All rats were fed 15 g of standard pellet per rat per day. Treatment oil and extract were administered by oral gavages. Rats in the menhaden group (MHD group, positive control, n = 10) were gavaged with 10 ml/kg menhaden oil per rat per day. Similarly 10 ml/kg of the C. striatus aqueous extract were given daily as oral gavages to each rat in the Haruan group (HRN group, n = 10). The rats in butter group (BTR group, n = 10) were treated with 10 ml/kg butter and rats in the control group (CTL group, n = 10) were the untreated controls. The individual body weights were recorded weekly to calculate their body weight gain during the trial. The baseline observation for spatial learning and memory were acquired using the Morris Water Maze (MWM) test at week-0 and re-evaluated after week 10. Blood collections were performed by cardiac puncture to determine the fatty acid composition in the plasma using gas chromatography after week-10. After ten weeks of treatment, there was a significant improvement (P < 0.05) in distance and time to reach the hidden platform in the MWM test of the rats in MHD and HRN group. Rats in the MHD group followed a shorter distance followed with the rats in HRN group, BTR group and lastly the rats in the CTL group. The same pattern of results was also observed for the time to reach the hidden platform. The rats in MHD group were fed a high level of docosahexaenoic acid (DHA, 22:6n-3 polyunsaturated fatty acids) which led to the better performance to reach the hidden platform as well as the rats in HRN group. The plasma of the MHD and HRN animals also had significantly increased (P<0.05) levels of n-3 PUFAs, at the end of the trial compared to both BTR and CTL groups. The results indicated that C. striatus aqueous extract supplementation produced a better performance in the MWM test and tissue fatty acid composition compared to the unsupplemented control.